2008
DOI: 10.1108/14725960810872622
|View full text |Cite
|
Sign up to set email alerts
|

Distractions in the workplace revisited

Abstract: Purpose -The purpose of this paper is to provide a holistic and systematic understanding of a fundamental issue within open plan office designs: the sustainability of two extremely contrasting requirements, concentration and collaboration, in the same workspace and work environment at a given time. A literature review is presented, along with initial suggestions for potential improvements in knowledge work organizations. Design/methodology/approach -A thorough range of fields, including those outside the built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Haynes (2007a) provides evidence supporting the fact that distraction is the component that has the most negative impact on perceived productivity and interaction has the most positive effect on perceived productivity. Office workers in most organisations wish to have distraction-free solo work and opportunities to have informal interaction with colleagues (Haynes, 2007b, Roper and Juneja, 2008, McCoy, 2002, Heerwagen et al, 2004, Chachere et al, 2003. The physical setting and layout of the workspace is part of organisational culture.…”
Section: Office Layoutmentioning
confidence: 99%
“…Haynes (2007a) provides evidence supporting the fact that distraction is the component that has the most negative impact on perceived productivity and interaction has the most positive effect on perceived productivity. Office workers in most organisations wish to have distraction-free solo work and opportunities to have informal interaction with colleagues (Haynes, 2007b, Roper and Juneja, 2008, McCoy, 2002, Heerwagen et al, 2004, Chachere et al, 2003. The physical setting and layout of the workspace is part of organisational culture.…”
Section: Office Layoutmentioning
confidence: 99%
“…Furthermore, employees could limit the ability for others to engage them in face-to-face collaboration by removing their bodies from the office and working in another place. (Heerwagen et al, 2004), they also have drawbacks such as distractions and lack of privacy (Roper & Juneja, 2008). With regard to this debate, Kim and de Dear (2013) a quiet space where you should avoid distracting others (rule schema), and knew the other people they were working with.…”
Section: Discussionmentioning
confidence: 99%
“…Bridger & Brasher, 2011;Roper & Juneja, 2008;Sundstrom, Town, Brown, Forman, & McGee, 1982). For example, Roper and Juneja (2008) argue that open-plan offices may heighten individual arousal and improve task performance via the social facilitation effect, but may also promote cognitive overload through crowding, office noise, distractions, and interruptions. Although some researchers have examined the social processes that create meaningful organisational spaces (e.g.…”
Section: Research Issuesmentioning
confidence: 99%
“…Not surprisingly, collocated workers experience more interruptions than distributed ones-62.9 percent versus 49.3 percent (Mark et al, 2005). Open-office designs foster auditory interruptions that interfere with complex tasks, cause concentration impairment, and reduce workplace performance (Roper & Juneja, 2008). Research has shown that the greater the task complexity, the more detrimental the noise distraction (Zaheeruddin & Garima, 2006).…”
Section: Distractions and Fragmentation In The Workplacementioning
confidence: 99%